The Potential of Averrhoa bilimbi Juice As An Alternative Reagent in Proteinuria Examination - Erna Kristinawati; Nutri Farda Nur; idyatul hasanah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
Background: Proteinuria indicates a kidney disorder and provides important prognostic information in diagnosing kidney disease. To determine the presence of protein in the urine, a urinalysis examination is carried out. Proteinuria examination generally uses the heating method with acetic acid, sulfosalicylic acid, and concentrated nitric acid as reagents. In Indonesia, the use of acetic acid for proteinuria examination is still the primary choice. An alternative reagent is needed that can replace the function of acetic acid. The objective of this study is to determine the potential of Averrhoa Blimbi juice as an alternative reagent for proteinuria examination.Methods: This was a Pre-experimental study with a completely randomized design. This study used urine samples from a patient with chronic kidney disease. Urine samples were examined using 6% acetic acid reagent as a control and using Averrhoa bilimbi juice with various concentrations. Each juice concentration was examined twice so that the experimental units in this study were 40 units. The Kruskal-Wallis test was used to determine the potential of Averrhoa bilimbi as an alternative reagent.Results: At concentrations of 5%-20% showed the same positive results as 6% acetic acid, namely +2, concentration 25%-35% resulted in +3, and other concentration resulted in +4. The results of data analysis showed p=0.04 (p<0.05). This shows that Averrhoa bilimbi has the potential as an alternative reagent for proteinuria examination.Conclusion: Averrhoa bilimbi juice with a 5%-20% concentration has the potential as an alternative reagent for 6% acetic acid to check proteinuria levels.Keywords: Averrhoa bilimbi ; alternative reagents; proteinuria; acetic acid; urinalysis